Independence of Student Learning on XI MIA-5 Class of SMAN 1 Kediri of PBL Models of Human Reproductive System Materials - Arum Sanjayanti; Sulistiono Sulistiono; Dwi Ari Budhiretnani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This study aimed to determine of learning independence with Problem Based Learning (PBL) learning models on the human reproductive system on XI MIA-5 class of SMAN 1 Kediri. Qualitative descriptive methode used to describe the ability of students to learn independently after the implementation of learning with PBL models. Indicators include independent learning confidence, responsibility, initiative and discipline in the form of a questionnaire compiled by Febriastuti (2013).  Student learning independence of XI MIA-5 class are taught by learning model Problem Based Learning (PBL) with good category, sufficient, and less, the percentages were 26, 60 and 10% respectively.Keywords: learning independence, PBL Models